Intelligent IoT-Enabled Roof Control System Using Mamdani Fuzzy Logic With Telegram-Based Remote Monitoring - Wulandari, Sholihah Ayu; Baihaqi, Ahmad; Asysyauqi, Haris; Ulla, Lya Nurul; Al ghifari, Mohammad Ghazi (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2025)
Automatic clothesline system is one of the solutions to the problem of clotheslines that are not due to sudden changes in weather, by using the esp8266 microcontroller it can be done to facilitate the community. This automatic clothesline system consists of esp8266 as a microcontroller, then a raindrop sensor as a rain detector and an ldr sensor as a sunlight detector. All components are assembled into a system to open and close the roof automatically, and users will also get notifications via telegram if the roof is open or closed. The results of this research show that the sensors work as expected, namely the roof can open and close automatically in rainy and dark conditions.